2005
DOI: 10.1016/j.rmed.2005.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic effects of sildenafil in patients with pulmonary arterial hypertension

Abstract: Sildenafil and inhaled nitric oxide (iNO) relax smooth muscle by inhibiting the degradation and stimulating the production of cyclic guanosine monophosphate, respectively. We compared the acute pulmonary vasodilator effects of sildenafil, iNO, and epoprostenol and asked whether the combination of iNO with sildenafil had additive pulmonary vasodilator effects. We assessed the effects of extended use of sildenafil in a small cohort of patients. Twenty patients with pulmonary arterial hypertension underwent an ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 28 publications
0
33
0
4
Order By: Relevance
“…There is substantial evidence that long-term treatment with other PDE5 inhibitors has a positive effect on antioxidant capacity, relief of symptoms, and restoration of erectile function in human and animal studies. For instance, sildenafil reduces malondialdehyde levels and potentiates the total antioxidant capacity of plasma in STZ-induced diabetic rats [29], induces symptomatic improvement in pulmonary hypertension [30] and prevents myocyte hypertrophy [31]. Moreover, erectile function, protein expression of phosphorylated eNOS and NOS enzymatic activity are improved in normal rats by sildenafil treatment [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…There is substantial evidence that long-term treatment with other PDE5 inhibitors has a positive effect on antioxidant capacity, relief of symptoms, and restoration of erectile function in human and animal studies. For instance, sildenafil reduces malondialdehyde levels and potentiates the total antioxidant capacity of plasma in STZ-induced diabetic rats [29], induces symptomatic improvement in pulmonary hypertension [30] and prevents myocyte hypertrophy [31]. Moreover, erectile function, protein expression of phosphorylated eNOS and NOS enzymatic activity are improved in normal rats by sildenafil treatment [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published study by Preston et al, 81 10 HF patients in NYHA classes III-IV were followed after an average course of 1271.6 months of sildenafil therapy. Six of the 10 patients reported improvement in NYHA functional score by at least one class and nine patients reported improvement in exertional dyspnea.…”
Section: Effects Of Chronic Pde-5i Usementioning
confidence: 99%
“…Preston et al 26 showed that in patients with acute and chronic PH, the addition of iNO potentates the pulmonary vasodilator effects of sildenafil lowering PVR more than each agent alone. 26 In patients who are candidates for heart/lung transplantation, the pulmonary vasodilator effects of oral sildenafil were found to be as effective as iNO, but it was more effective when the 2 were combined.…”
Section: Matamis Et Al Ino and Sildenafil In Cardiac Surgery Patients 51mentioning
confidence: 99%
“…Preston et al 26 showed that in patients with acute and chronic PH, the addition of iNO potentates the pulmonary vasodilator effects of sildenafil lowering PVR more than each agent alone. 26 In patients who are candidates for heart/lung transplantation, the pulmonary vasodilator effects of oral sildenafil were found to be as effective as iNO, but it was more effective when the 2 were combined. 27 These additive effects induced by the combination of the 2 drugs may indicate a synergistic effect, providing pulmonary vascular smooth muscle relaxation due to mechanisms mediated by cGMP.…”
Section: Matamis Et Al Ino and Sildenafil In Cardiac Surgery Patients 51mentioning
confidence: 99%